Militerisasi Perbatasan antara Negara Amerika Serikat dengan Negara Kanada setelah Serangan Teroris 9/11 - Fransiscus Primus Hernata; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Good relations between the United States and Canada can be said as one of the best relations between countries in the world, this is based on several factors such as similar cultural values, shared political interests, intimate diplomatic relations, and strong economic relationship. At first the border between the United States and Canada was a symbol of good and intimate relations between the two countries so that there was no security at all at the border between the two countries, but this has changed since the 9/11 terrorist attacks. This incident has changed the views of the public and policy makers towards terrorist attacks, this incident has changed national assumptions about terrorism, especially those related to domestic security. After the 9/11 terrorist attacks, migration has become a topic that can be related to terrorism because terrorists can enter a country through immigration gates for residents of a country. The research was made through the collection of qualitative data, as well as through the concept of securitization. This research analyzes the forms of securitization carried out by the United States after the 9/11 incident. The results of this study are that there are many policy changes on the border between the United States of America and Canada after the 9/11 terrorist attacks, this is proven by the Smart Border Action Plan policy which was signed in December 2001 right after the terrorist attack occurred. signifies the urgency to secure the border between the two countries